2004
DOI: 10.1073/pnas.0308753101
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of acid-sensing ion channel 1a in transgenic mice increases acquired fear-related behavior

Abstract: The acid-sensing ion channel 1a (ASIC1a) is abundantly expressed in the amygdala complex and other brain regions associated with fear. Studies of mice with a disrupted ASIC1 gene suggested that ASIC1a may contribute to learned fear. To test this hypothesis, we generated mice overexpressing human ASIC1a by using the panneuronal synapsin 1 promoter. Transgenic ASIC1a interacted with endogenous mouse ASIC1a and was distributed to the synaptosomal fraction of brain. Transgenic expression of ASIC1a also doubled neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(159 citation statements)
references
References 54 publications
8
146
1
4
Order By: Relevance
“…6,7 ASIC1a in particular is involved in nociception and fear behavior triggered by hypercapnia. 8,9 ASICs have also been investigated as new targets for the treatment of ischemic stroke and cerebral hypoxia 10 on the premise that activation of ASIC1a during ischemia may cause neuronal cell death through toxic Ca 2 þ and Na þ influx. 10,11 Metabolic acidosis can occur as a result of lactate accumulation when tissue perfusion is inadequate, or when mitochondrial respiration is inhibited.…”
mentioning
confidence: 99%
“…6,7 ASIC1a in particular is involved in nociception and fear behavior triggered by hypercapnia. 8,9 ASICs have also been investigated as new targets for the treatment of ischemic stroke and cerebral hypoxia 10 on the premise that activation of ASIC1a during ischemia may cause neuronal cell death through toxic Ca 2 þ and Na þ influx. 10,11 Metabolic acidosis can occur as a result of lactate accumulation when tissue perfusion is inadequate, or when mitochondrial respiration is inhibited.…”
mentioning
confidence: 99%
“…It will be interesting to determine how these genes and their pathways interact, as many of the mechanisms underlying learning and memory appear to be conserved. For example, mammalian ASIC-1 is involved in learned fear (Wemmie et al 2004), and a SNP in casy-1 ortholog, calsyntenin-2, has been linked to human memory performance (Papassotiropoulos et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The role of mammalian ASIC-1 in learning (Wemmie et al 2002(Wemmie et al , 2004 prompted Voglis and Tavernarakis (2008) to study its C. elegans homolog. They found that asic-1 mutants were impaired in isothermal tracking as well as associative learning assays pairing chemosensory cues with food or starvation.…”
Section: Asic-1mentioning
confidence: 99%
“…A bioinformatic search of the chromosome segment comprising the 17q11.2-q12 region suggested the ACCN1 gene as the most interesting gene, as the acid-sensing ion channels (ASICs) may be involved in anxiety-related pathways. [25][26][27] The ACCN1 gene comprises a genomic region of approximately 1. Figure 1 An overview of the study design: in stage 1, we conducted a genome-wide scan, which detected significant association between PD and a twomarker segment (D17S1294-D17S1293) on chromosome 17.…”
Section: Genotypingmentioning
confidence: 99%